JURIDICAL STATUS OF STOCK EXCHANGE AND INVESTOR LEGAL PROTECTION IN FORCED DELISTING - Ayu Atha Diva Daniswara; I Wayan Novy Purwanto (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2022)
The Stock Exchange has a role as a regulator of securities trading in the capital market. The Stock Exchange works for profit which is then aimed at developing securities trading activities in the capital market. Meanwhile, there is no form of legal protection for investors in the capital market which is specifically regulated in the law. The purpose of this study is to examine the juridical status of the stock exchange and to determine the legal protection for investors in the implementation of forced delisting. This study uses a normative legal research method, which is sourced from the Legislation by using a library research method. The results reveal that the Juridical status of the Stock Exchange is a company that has its own working rules, so it has differences compared to companies in general, and there is no form of protection for stock investors who experience forced delisting of issuers on the stock exchange. Investors are only given the opportunity to make sales in the negotiated market whose time is determined by the exchange. The findings of this research provide an explanation of the legal protections afforded to investors in the event that forced delisting is implemented.